Dropping out of the labor force :|women in Turkey - Genç, Yazğı. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
According to the microdata of Household Labor Force Survey (HLFS) in 2017, the half amount of women are not in the labor force even though they are not disabled, retired or students. The share of the women who have worked before and who are no longer in the labor force substantially increased from 24.4 percent to 31.7 percent in the period of 2010-2017. As the share of women who dropped out women increased, the share of women who are not in the labor force and have never worked before substantially decreased by 18.0 percentage points and recorded at 19.2 percent in 2017. The data implies that women have more problems staying in labor force than entering it. I find that being married, having a child aged between 0 and 5 and having low education levels women increase the likelihood of labor market exit. Also, working in agriculture, the sector of other services, and elementary occupations or as craft workers, plant and machine operators, and assemblers increases the probability of labor market exit. Lastly, I examined the dropping out of the labor market exit by education levels. I find that marginal effect of the last sector is similar across education levels while the effect of occupational groups are different for women in every education levels.
Keywords: Labor supply -- Turkey.; Women -- Turkey.